1996
DOI: 10.1161/01.str.27.7.1205
|View full text |Cite
|
Sign up to set email alerts
|

Dementia After First Stroke

Abstract: Dementia is relatively frequent after a clinical first stroke in persons younger than 80 years, and aphasia is very often associated with poststroke dementia. If aphasic patients are not considered, it may be necessary to screen a very large number of subjects to collect an adequate sample of demented cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
179
9
9

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(216 citation statements)
references
References 43 publications
18
179
9
9
Order By: Relevance
“…For some evidences, an atrial fibrillation was relevant to cognitive impairment and hippocampal atrophy with no symptomatic stroke or silent infarction. 34,35 The previous studies 26,30,31,[36][37][38][39] and the results of our study have shown that atrial fibrillation was associated with an increased risk of poststroke dementia. Moreover, the result of this study found that stroke patients with atrial fibrillation risk of dementia were 1.68 times compared with stroke patients without atrial fibrillation statistically significant.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…For some evidences, an atrial fibrillation was relevant to cognitive impairment and hippocampal atrophy with no symptomatic stroke or silent infarction. 34,35 The previous studies 26,30,31,[36][37][38][39] and the results of our study have shown that atrial fibrillation was associated with an increased risk of poststroke dementia. Moreover, the result of this study found that stroke patients with atrial fibrillation risk of dementia were 1.68 times compared with stroke patients without atrial fibrillation statistically significant.…”
Section: Discussionsupporting
confidence: 53%
“…48 Diabetes mellitus has been associated with various adverse health effects, and it was found that patients with diabetes mellitus were more likely than normal patients to have low MMSE 49 reduced cerebral blood flow associated with impaired cerebral auto regulation, increased blood viscosity, and greater prevalence of underlying intracranial large-or small-artery disease. 50 Similarly, the reported association between stroke patients with and without diabetes mellitus of other studies 20,21,26,30,31,39,46 found that diabetes mellitus associated with an increased prevalence of post-stroke dementia. The present study showed that stroke patients with diabetes mellitus risk of dementia were 1.25 times compared with stroke patients without diabetes mellitus statistically significant.…”
Section: Reviewmentioning
confidence: 89%
“…We censored TICS-m scores occurring after incident strokes, because stroke increases the risk for cognitive impairment and dementia. 20,50 Anemia and certain medications can cause cognitive dysfunction, and both are seen commonly in CKD, so we carried out secondary analyses adjusting for baseline hematocrit and psychoactive medication use. Analyses were conducted with SAS 9.1.3 software (Cary, NC).…”
Section: Discussionmentioning
confidence: 99%
“…[138][139][140][141]143 Prevalence rates vary between 13.6% 140 and 31.8% 142 at 3 months. Kokmen et al (1996) 138 have shown that the cumulative incidence of dementia in a stroke cohort increased from 7% at year 1 to 48% at year 25.…”
Section: Post-stroke Dementiamentioning
confidence: 99%
“…144 As shown in Table 6, 5.5 to 16.3% of patients admitted for stroke seem to have had undetected pre-existing progressive cognitive decline. 138,142,[144][145][146][147] Risk factors for post-stroke dementia At least three different groups of factors, each acting independently, rather than a single pathophysiological mechanism probably contribute to the development of post-stroke dementia: 111,148 (1) stroke-related factors such as the location and the severity of the brain lesions; 149,150 (2) the overall cardiovascular risk profile as determined by the presence of atrial fibrillation 140 or diabetes mellitus; 149 (3) non-strokerelated factors similar to those found in Alzheimer's disease including increasing age, 149,151 low education, 149 cortical atrophy. 145,152 Hypertension has been identified as a risk factor by Pohjasvaara et al (1998), 111 but not by Skoog et al (1996).…”
Section: Post-stroke Dementiamentioning
confidence: 99%